Statement of Peer Review - Majid Ali; Muhammad Ashraf Javid; Shaheed Ullah; Iqbal Ahmad (Engineering Proceedings, 2023)
In submitting the proceedings of the 5th Conference on Sustainability in Civil Engineering (CSCE) to Engineering Proceedings, the volume editors of the proceedings certify to the publisher that all papers published in this volume have been subjected to peer review administered by the volume editors [...]